How can we make research more relevant for sport practice? - Haugen, T. (International Journal of Sports Physiology and Performance, 2024)
Coaches and athletes aim to enhance performance. Performance in sport is determined by a complex interaction of numerous underlying variables that require various stimuli. Application of fundamental training principles, training forms, and training methods and manipulation of loading factors constitute the cornerstones of most training philosophies. Coaches apply a holistic and athlete-centered approach wherein planning and execution of training take individual predispositions and environmental factors into account.5 Through trial and error, they possess in-depth knowledge related to what kind of training should be performed at a given time or situation for each particular athlete, without necessarily possessing in-depth knowledge regarding the underlying mechanisms.